Trophic egg laying: hypotheses and tests - Perry, J; Roitberg, B (2006)
Trophic egg-laying - wherein mothers provide non-developing eggs for offspring to eat - has attracted much empirical attention to diverse taxa (e.g. amphibians, non-social and eusocial insects, fish, and marine gastropods). However, there has been been only a limited exchange of ideas among studies of different taxa. We advocate a unified approach to the study of trophic eggs within an evolutionary ecological framework. In this paper, we stress the importance of elucidating the adaptive function of trophic eggs through explicit hypothesis testing, and our primary objective is to outline key experiments that can test adaptive and functional hypotheses. Currently, some cases of hypothesized trophic eggs may simply represent offspring consumption of eggs that failed to develop for non-adaptive reasons (e.g. sperm limitation). Furthermore, in many trophic egg-laying species, it is unclear whether trophic eggs have evolved to provision offspring or to reduce cannibalism among offspring. With increased focus on theory and hypothesis testing, the study of trophic eggs can offer important insight into topics such as sibling rivalry, parent-offspring conflict, and parental care.